Factors Affecting Real Earnings Management Through Discretionary Cost - Octavia, Meliana; Subekti, Imam; Mardiati, Endang (International Journal of Social and Local Economic Governance, 2015)
The main goal of this research is to investigate the effect of corporate social responsibility disclosure, leverage, return on assets, and growth to real earnings management from discrectionary cost, with political cost as moderating variable. Samples of this research are 94 random listed companies which were selected by purposive method. The results of this research are: corporate social responsibility disclosure and growth have negative effect to real earnings management through discretionary cost, leverage and return on asset have positive effect to real earnings management through discretionary cost, political cost does not affect the relation between corporate social responsibility disclosure and growth to real earnings management through discretionary cost, and political cost may weaken the positive effect of leverage and return on asset to real earnings management through discretionary cost.Keywords: real earnings management, discretionary cost, corporate social responsibility disclosure, leverage, return on asset, and growth